Learning Implementation with RUBA Interactive Multimedia-Based to Beginner Reading - Zulmiyetri, Zulmiyetri; Iswari, Mega; Rahmahtrisilvia, Rahmahtrisilvia; Irdamurni, Irdamurni; Nurhastuti, Nurhastuti; Rumapea, Monica (Journal of Education for Sustainability and Diversity, 2023)
Beginning reading is an early stage ability that must be mastered. However, problems are still often found in elementary schools (SD), there are students who have difficulty reading the beginning. For this reason, appropriate solutions are needed so that students can be help improve their initial reading skills. At SD Negeri 02 Koto Tangah Tilatang Kamang, the teacher provides a solution related to the problem of students who have difficulty learning to read at the beginning by using interactive multimedia learning media RUBA (reading room) which has been proven to be effective. For this reason, it is necessary to conduct research to find out how the implementation of these media in learning to read begins. This research was conducted with a qualitative approach and the type of research was descriptive by collecting data through observation and interviews. The results of this study are the implementation of early reading learning based on interactive multimedia by the teacher can increase TPACK competence, especially competence in technology, which impacts the emergence of children’s enthusiasm in learning.